Natural Durability of Five Bamboo Species Against Termites and Powder Post Beetle - Fauzi Febrianto; Adiyantara Gumilang; Sena Maulana; Imam busyra; Agustina Purwaningsih (Masyarakat Peneliti Kayu Indonesia, 2014)
Bamboo is multipurpose plant and is traditionally used by Indonesian rural community to substitute wood for housing material. Bamboo is susceptible to termite and powder post beetle. Consequently, bamboo and its derivative products have relatively short service life. Most available information regarding the natural durability of bamboo in Indonesia was acquired based on various different methods and are less accurate. The present research was aimed to analyze the natural durability of ampel bamboo (Bambusa vulgaris Schrad. Ex Wendl), betung bamboo (Dendrocalum asper), andong bamboo (Gigantochloa verticillata), hitam bamboo (Gigantochloa atroviolaceae) and tali bamboo (Gigantochloa apus)) against subterranean termite (Coptotermes curvignathus), dry wood termite (Cryptotermes cynocephalus), and powder post beetle (Anobium sp) referring to SNI 01.7207-2006. The results showed that bamboo species determined its natural durability against C. curvignathus, C. cynocephalus and Anobium sp. Natural durability of tali bamboo, betung bamboo, and hitam bamboo against C. curvignathus belonged to the 2nd class (resistant), while andong bamboo and ampel bamboo belonged to the 4th class (poor). Natural durability of non-barked hitam bamboo, and andong bamboo against C. cynocephalus belonged to the 3rd class (medium), while those of tali bamboo, betung bamboo, and ampel bamboo belonged to the 4th class (poor). Natural durability of all barked bamboos species against C. cynocephalus were categorized to the 4th class (poor). The resistance of ampel bamboo and andong bamboo against Anobium sp were lower compared to those of tali bamboo, hitam bamboo, and betung bamboo.Keywords: bamboo, dry wood termite, natural durability, powder post beetle, subterranean termite